Pengaruh Green Accounting Terhadap Nilai Perusahaan - Siera Fini; Christina Dwi Astuti (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to examine and analyze the effect of green accounting, green intellectual capital and carbon emission disclosure on firm value. This type of research is quantitative research using secondary data. The population in this study are companies in the energy and industrial sectors listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The sample of this research is 441 obtained by purposive sampling method. The analytical method used is panel data regression analysis. The statistical tool used is SPSS. The results of this study show that green accounting have a positive effect on firm value, but green intellectual capital and carbon emission disclosure don’t have an effect on firm value. Keywords: Green Accounting; Green Intellectual Capital; Carbon Emission Disclosure; Firm Value